Hurricane Season Forecast 2013 - Szatkowski, Gary (My University, 2013)
Mr. Szatkowski described the 2012 hurricane season. In 2012 there were 19 named storms, 10 reached hurricane strength and 2 were major hurricanes. This exceeded the average number. This year is likely to exceed last year because the ACE, Accumulated Cyclone Energy is estimat- ed to be higher than last year. The forecast has not been released from the Hurricane Center yet, but it can be expect to be an above average active season. Mr. Szatkowski cautioned that the U. S. is experiencing the longest period without a major hurricane striking land based on long term averages. Chances are that we can expect a major hurricane before long.
Keywords: Hurricanes; Emergency management; NCEM; Emergency disaster